PRESENT DAY DEFORMATION IN THE EAST VIETNAM SEA AND SURROUNDING REGIONS - Trinh, Phan Trong; Liem, Ngo Van; To, Tran Dinh; Huong, Nguyen Van; Hai, Vy Quoc; Thom, Bui Van; Phong, Tran Van; Vinh, Hoang Quang; Xuyen, Nguyen Quang; Thuan, Nguyen Viet; Tuc, Nguyen Dang; Thuan, Dinh Van; et al. (Vietnam Journal of Marine Science and Technology, 2015)
This paper presents velocities of present-day tectonic movement and strain rate in the East Vietnam Sea (South China Sea) and surroundings determined from GPS campaigns between 2007 and 2010. We determine absolute velocities of GPS stations in the ITRF05 frame. The result indicates that GPS stations in the North of East Vietnam Sea move eastwards with the slip rate of 30 - 39 mm/yr, southwards at the velocities of 8 - 11 mm/yr. Song Tu Tay offshore moves eastwards at the rate of ~24 mm/yr and southwards at ~9 mm/yr. GPS stations in the South of East Vietnam Sea move to the east at the rate of ~22 mm/yr and to the south at the velocities of 7 - 11 mm/yr. The effect of relative movement shows that the Western Margin Fault Zone activates as left lateral fault zone at the slip rate less than 4 mm/year.In Western plateau, the first result from 2012 - 2013 GPS measurement shows that the velocities to the east vary from 21.5 mm/yr to 24.7 mm/year. The velocities to the south vary from 10.5 mm/yr to 14.6 mm/year. GPS solutions determined from our campaigns are combined with data from various authors and international projects to determine the strain rate in the East Vietnam Sea. Principal strain rate changes from 15 nanostrain/yr to 9 nanostrain/yr in the East Vietnam Sea. Principal strain rate and maximum shear strain rate along the Red River Fault Zone are in order of 10 nanostrain/year. East Vietnam Sea is considered to belong to the Sunda block.